Diversity of microbiological pathogens in diabetic foot ulcers in an African population - Oyan, Boma; Abere, Sarah; Gomba, Victoria Eno; Lawson, Stephenson; Okoli, Nkemegbunam; Tonye-Abere, Orabelema (International Journal of Research in Medical Sciences, 2023)
Background: Diabetic foot ulcer is a devastating complication of diabetes and the commonest cause of non-traumatic amputation worldwide. It constitutes a huge socioeconomic burden to the patient and health care system. The aim of this study was to determine the spectrum of bacterial isolates cultured from diabetic foot ulcers and assess their in vitro susceptibility to commonly used antibacterial agents. Methods: The study was a retrospective descriptive study where records of all diabetic foot ulcer samples sent to the microbiology department for microscopy, culture and sensitivity between January 2020 to December 2021 were extracted. The bacteriological isolation and antimicrobial sensitivity tests of the isolates was carried out by standard microbiological methods. Results: A total of sixty-one patients results were retrieved and included in this study. The commonest organism isolated was Staphylococcus aureus which constituted almost half 40 (46.0%) of the organisms isolated, followed by Escherichia coli and Proteus mirabilis which accounted for 23.0% and 18.4% respectively of the organisms. Pseudomonas aeruginosa was the least common organism and was seen in only 3 (3.4%) samples. Concerning antibiotic sensitivity, 55.0% of S. aureus, 50.0% of K. pneumoniae, 60.0% of E coli and P. mirabilis were sensitive to cefpodoxime whereas 50.0% of S. aureus and K. pneumoniae, 90% of E coli and 68.8% of P. mirabilis were sensitive to cefuroxime. Conclusions: Diabetic foot ulcers are infected with polymicrobial organisms and S. aureus was the predominant organism isolated. However, there is an emerging pattern in the spectrum of antibiotic sensitivity which is an important consideration in management.